Juridical Aspects Of Protecting Students And Teaching Staff From Sexual Violencein Higher Education - Abd. Sani, Muh. Adriansyah; Akili, Rustam Hs.; Moonti, Roy Marthen (International Journal of Law, Crime and Justice, 2025)
Sexual violence in the university environment is a significant challenge in creating a safe and supportive educational atmosphere. This phenomenon is influenced by unequal power relations, patriarchal culture, and lack of understanding and application of legal protection. Regulation of the Minister of Education, Culture, Research and Technology Number 30 of 2021 is presented as a legal framework to prevent and handle sexual violence in higher education, with strategic steps such as the formation of the Task Force for the Prevention and Handling of Sexual Violence (PPKS Task Force). This research aims to examine the juridical aspects of protecting students and teaching staff from sexual violence, analyze the implementation of regulations, and identify obstacles faced in their implementation. This research uses a normative-juridical method, which prioritizes the analysis of laws and regulations, legal documents, and related legal theories. The results show that although the regulation has provided quite detailed guidelines, its implementation still faces challenges in the form of social stigma, lack of resources, and gaps between policy and practice. The conclusion of this study emphasizes the importance of continuous evaluation and education to improve the effectiveness of regulations and encourage universities to become agents of change in the fight against sexual violence.